Creatine supplementation improves sprint performance in male sprinters - Skare, O. C.; Skadberg ,O.; Wisnes, A. R. (Scandinavian Journal of Medicine & Science in Sports, 2001)
The object of this study was to evaluate the effect of creatine (Cr) supplementation in well trained male sprinters. The study was performed as a single blind test on 18 sprinters at a local competition level. During the last two years a substantial part of their training had consisted of a series of maximal sprints with short rest periods to improve their fatigue resistance. The participants consumed either 20 g Cr+20 g glucose per day (Cr group, n=9) or 40 g glucose per day (placebo group, n=9), divided into 4 equal dosages. The effect of Cr on sprint performance was evaluated in two tests, 1 x 100 m sprint and an intermittent 6x60 m sprint. Cr supplementation increased the 100 m sprint velocity (11.68+/-0.27 s vs 11.59+/-0.31 s) and reduced the total time of 6 intermittent 60 m sprints (45.63+/-1.11 s vs 45.12+/-1.1 s), whereas no changes were observed in the placebo group. The sprint velocity was significantly increased in 5 out of 6 intermittent 60 m sprints. Venous blood was drawn 5 min after finishing the final intermittent 60 m run. Plasma lactate, Cr and serum creatinine (Crn) were all increased in the Cr group compared to presupplementation values; no changes were observed in the placebo group. The improved sprint performance suggests an increased availability of energy substrate for performing work, possibly as a result of increased skeletal muscle creatine phosphate (PCr).